Prolonged intralymphatic delivery of dendritic cells through implantable lymphatic ports in patients with advanced cancer. Issue 1 (19th April 2016) - Radomski, Michal; Zeh, Herbert J.; Edington, Howard D.; Pingpank, James F.; Butterfield, Lisa H.; Whiteside, Theresa L.; Wieckowski, Eva; Bartlett, David L.; Kalinski, Pawel
Abstract : Background: The currently-used modes of administration of immunotherapeutic agents result in their limited delivery to the lymph nodes and/or require repetitive ultrasound-guided nodal injections or microsurgical lymphatic injections, limiting their feasibility. Here, we report on the feasibility and safety of a new method of long-term repetitive intralymphatic (IL) infusion of immune cells, using implantable delivery ports. Methods: Nine patients with stage IV recurrent colorectal cancer underwent complete resection and received autologous dendritic cells (DCs) loaded with killed autologous tumor cells, KLH and PADRE, for up to four monthly cycles. Leg lymphatic vessels were cannulated, connected to 6.6Fr low-profile implantable subcutaneous delivery ports, and used to infuse 12 doses of DC over each 72 h-long cycle (every 6 h), followed by heparin flushes of the cannula-port system (one 72 h-long cycle per month). The patients who opted for alternative route of vaccine administration (2 patients) or whose ports became non-functional between cycles, continued treatment via intranodal (one injection/cycle) or intradermal (four injections/cycle) routes. Results: A total of nine lymphatic cannulations and implantations of subcutaneous delivery ports were attempted in seven patients, with a success rate of eight out of nine (89 %). The average patency of the IL delivery system was 7.5 (±3.2) weeks. All six patients with IL ports successfully completed at least one complete 72 h-long DC infusion cycle (12 injections). Five patients (56 %) completed two full IL cycles (24 IL injections). No patients received more than two IL cycles without replacement of the IL port, due to catheter occlusion and/or local side effects: cellulitis and hematoma. Intranodal and intradermal backup options were used in, respectively, one and two patients. Overall cohort survival was >28 (±25) months. One patient with aggressive recurrent carcinomatosis, who received DC vaccines by intranodal route is alive at > 90 months, without evidence of disease. Conclusions: We conclude that an intermediate-duration IL delivery of multiple doses of immunotherapeutic factors using implantable delivery ports is feasible, highly-tolerable and can be reproducibly performed in cancer patients to administer immune cells, or potentially, other immune factors. However, long-term IL port placement (>7.5 weeks), is not a currently-feasible option. Trial registration: NCT00558051, registered Nov. 13, 2007.